ANALISIS DESAIN SISTEM : APLIKASI CEKLIST AKREDITASI PROGRAM STUDI - Buhori, Buhori; Razzaq, Nurfathan Samnaufal; Fahmi, Fiqih Zulfikar; Armawaddin, Irsyad Daffa (Journal of Digital Business and Innovation Management, 2023)
This research aims to analyze the system design of the checklist application accreditation. This application facilitates the data collection process and accreditation assessment in organizations. Analysis is carried out on the operational and organizational aspects of the application, as well as the possible impacts during the development process. The analysis also includes a summary of development, system weaknesses and limitations, and alternatives and trade-offs considered in the application design.